Determinants of compassion satisfaction, compassion fatigue and burn out in nursing: A correlative meta-analysis. Issue 26 (June 2018) - Zhang, Ying-ying; Zhang, Cheng; Han, Xiao-Rong; Li, Wei; Wang, Ying-lei
Abstract: Background: Compassionate care is essential for better clinical and patient outcomes, but during healthcare provision it can be compromised by several factors. This study evaluates factors affecting compassion satisfaction, compassion fatigue and burnout in nursing. Methods: Literature search in electronic databases was followed by data extraction, conversion, and meta-analyses under random effect model. Correlation coefficients ( r ) reported by individual studies were first converted to z- scores for meta-analyses and the overall effect sizes were then back-transformed into r. Results: Eleven studies (4054 respondents; 64.34 [95% confidence interval: 38.82, 89.86] % response rate; age 39.81 [31.36, 48.27] years; 87.11 [79.48, 94.73] % females) were used for meta-analysis. There was a strong positive correlation between compassion fatigue and burnout ( r =  0.59), whereas compassion satisfaction had weak negative correlation with compassion fatigue ( r =  −0.226) but moderate with burnout ( r =  −0.446). Stress and negative affect were moderately positively associated with compassion fatigue ( r =  0.405) but weakly correlated with burnout ( r =  0.119). Positive affect and personal/social factors had weak inverse relationship with burnout ( r =  −0.197). Positive affect also had a moderately positive relationship with compassion satisfaction ( r =  0.396). Demographic or professional factors were not significantly related to compassion satisfaction, compassion fatigue, or burnout. Conclusion: In nursing, a variety of stressful factors and negative affect promote compassion fatigue and burnout whereas positive affect is helpful in achieving compassion satisfaction. Abstract : Supplemental Digital Content is available in the text